2018
DOI: 10.1186/s40468-018-0067-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Japanese teachers’ classroom English “internationally”: implications for the development of classroom English language benchmarks in Japan

Abstract: Background: This study aims to develop a low-stakes assessment tool to establish a classroom English language benchmark that Japanese teachers of English can use for their own professional development purposes. To start with, we describe the differences between CLA (Classroom Language Assessment) in Hong Kong and the IDS (Integrative Diagnostic Scale) in Japan with regard to agenda, characteristics, and implementation. Then, we report findings made from both of these assessment types and from a group discussio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Such retraining should be aimed to improve their language proficiency. This particular retraining program have been implemented by a number of Asian countries to push their NNEST to achieve the required English proficiency based on universally acceptable standard such as CEFR albeit with varying degrees of success (Coniam et al, 2017;Nakata et al, 2018;Pham, 2018). The finding also seems to steer towards the retraining of NNEST to improve their General English Proficiency, instead of their Classroom English Proficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such retraining should be aimed to improve their language proficiency. This particular retraining program have been implemented by a number of Asian countries to push their NNEST to achieve the required English proficiency based on universally acceptable standard such as CEFR albeit with varying degrees of success (Coniam et al, 2017;Nakata et al, 2018;Pham, 2018). The finding also seems to steer towards the retraining of NNEST to improve their General English Proficiency, instead of their Classroom English Proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The finding also seems to steer towards the retraining of NNEST to improve their General English Proficiency, instead of their Classroom English Proficiency. NNEST errors in writing showed that they still have problems with their general English and not just isolated to the English used in classroom interaction or the English used in teaching English (Freeman, 2017;Nakata et al, 2018;Pham, 2018;Renandya et al, 2018;Richards, 2017). By providing retraining in General English Proficiency, NNEST will be able to improve their overall English proficiency and became better English user themselves and fulfill their role as proper language models for their students.…”
Section: Discussionmentioning
confidence: 99%
“…People who often watch Japanese anime will find out that there are many words in Japanese that are borrowed from English and when Japanese pronounce those words or speak English, many of them have accents. It wouldn't be a problem that people speak with an accent unless the accent has an effect on people's comprehension [3]. Native Japanese speakers usually make some the last consonant of the stress and secondary stress in a word voiced and add a /ɔ/ after the voiced consonant.…”
Section: Japanese and Frenchmentioning
confidence: 99%
“…Pedagogical competency has been primary attention while doing professional development programs. In this way, in-service teachers will not overlook the other prominent aspects in teaching comprising instructional goal (Avila Fernandez 2016), knowledge of content (Anugerahwati and Saukah 2010), content presentation (Nurkolis, Warastuty, and Yuliejantiningsih 2020), pedagogical knowledge (Bayram and Bıkmaz 2021), and also assessment skills (Nakata et al 2018) (Ibrahim and Kavlu 2020). In a nutshell, professional MGMP as a teachers' forum is inevitably expected to help teachers mitigate their hurdles in conducting the teaching and learning process daily.…”
Section: Paper Type -Research Papermentioning
confidence: 99%